(untitled) (Fiep Bulletin - online, 2013)
This article makes an abbreviation bibliographical revision on the alimentary upset and the media, and the influence that this can cause in the perception of the corporal image in diseases as nervous anorexia and nervous bulimia. At the end, we verified that the media influences yes in the perception of the women’s corporal image, however it is not the only criminal. As it was observed other factors that aid in the emergence of the alimentary upset exist